Postoperative Self-Report of Pain in Children: Interscale Agreement, Response to Analgesic, and Preference for a Faces Scale and a Visual Analogue Scale - Clément de Tovar; Carl L von Baeyer; Chantal Wood; Jean-Pierre Alibeu; Malik Houfani; Charles Arvieux (Pain Research and Management)
OBJECTIVE: To augment available validation data for the Faces Pain Scale – Revised (FPS-R) and to assess interscale agreement and preference in comparison with the Coloured Analogue Scale (CAS) in pediatric acute pain.